SISTEM PEMERINTAHAN KEMENDAPOAN DI WILAYAH ADAT TIGO LUHAH SEMURUP 1979 – 2022 - Sintiya Julianti; Abdul Salam (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This reasearch is a culttural history study that discusses the Kemendapoan government system in the Semurup customary area in 1979-2020. The purpose of this study is to find out the backround of the establishment of the traditional Kemendapoan government system in the Semurup customary area in 1979-2020 and how the concept and function of Kemendapoan change in Semurup in 1979-2020. The study uses the historical method which consist of four steps, namely heuristics, verification, interpretation, and hostoriography. The result of this study after being issued UU No. 5 Tahun 1979 about village government, the Kemendapoan was abolished and residance with village government but the functions and concept are still used in Semurup, known as the Semurup customary government. In this government, traditional leaders still play an important role in the order of people’s lives. The background for the establishment of the Kemendapoan was to regulate customary territories led by the Depati, this customary territory consists of several hamlets that originate from the same ancestor. The Kemendapoan government has existed since the 17M, then passed on by the Netherlands during the colonial period. Kemendapoan formed a government based on a customary system so that the Depati not rebel against the Netherlands.